1983
DOI: 10.3109/00016358309162334
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory efficiency

Abstract: One of the purposes of mastication is to break down the food and enlarge the area of food particles. A method is described by which the masticatory efficiency is estimated by calculating the area of a chewed test material, gelatin-hardened by formalin. When test pieces, after being chewed, are placed in a water-soluble dye, the dye will diffuse into the particles, and consequently the dye concentration in the surrounding solution will decrease. The concentration of the dye solution is read from a photometer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Several studies (Helkimo, Carlsson & Helkimo, 1978;Chauncey et al, f 981) found that the objective chewing performance decreases with the number oi teeth and age. Elderly people need more chewing strokes before the swallowing threshold is reached and the particle size is bigger when swallowing (Agerberg & Carlsson, 1981;Gunne, 1985;Idowu, Graser & Handelman, 1986). For these reasons one would expect a lower percentage of subjects in this study who are satisfied with their chewing ability, but this was not found.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Helkimo, Carlsson & Helkimo, 1978;Chauncey et al, f 981) found that the objective chewing performance decreases with the number oi teeth and age. Elderly people need more chewing strokes before the swallowing threshold is reached and the particle size is bigger when swallowing (Agerberg & Carlsson, 1981;Gunne, 1985;Idowu, Graser & Handelman, 1986). For these reasons one would expect a lower percentage of subjects in this study who are satisfied with their chewing ability, but this was not found.…”
Section: Discussionmentioning
confidence: 99%
“…A wide literature about chewing ability is available and many variables have been studied. For overviews, see work by Bates and colleagues [10] and Gunne [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term masticatory efficiency is commonly used to describe the number of masticatory cycles required to reduce ingested food to swallowable pieces, whereas masticatory performance refers to the particle size distribution of food chewed after a standardized number of cycles [ [15] , [16] , [17] ]. For masticatory efficiency evaluation, the “sieve method” is one of the most common techniques, based on the collection and assessment of particles from previously masticated food [ [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Mastication is affected, among others, by the occurrence of malocclusion, skeletal configuration, consistency of food, and number of functional teeth.…”
Section: Introductionmentioning
confidence: 99%